Comparison of Platelet Rich Plasma Dressing with Conventional Saline Dressing on Spoke Wheel Injury Wounds in Pediatric Patients: A Randomized Controlled Trial - Zahid, Hira; Sharif, Muhammad; Fatima, Batool; Janjua, Azwa; Iftikhar, Muhammad Adil; Zafar, Zuha (Indus Journal of Bioscience Research, 2024)
Objectives: To compare the outcome of topical Platelet Rich Plasma (PRP) dressing versus normal saline dressings on Wheel spoke injury (WSI) wounds in terms of duration of wound healing, wound infection, pain and need for hospital stay. Methods: It was a Randomized controlled trial conducted in Department of Pediatric Surgery KEMU/Mayo Hospital Lahore from September 2023 to August 2024. Children 12 years of age or younger presenting with WSI having an open wound which was allowed to heal by secondary intention were included in the study. Group A got normal saline soaked dressing daily and group B was given topical PRP dressing. The PRP rich gel layer obtained after centrifuging patients’ own blood sample was applied on wound. This was done once weekly for maximum 4 sessions. Variables like duration of wound healing, wound infection and pain along with other parameters were recorded. Results: Our sample consisted of total 69 patients 34 were Group A as control and 35 were Group B as cases. Mean age was 8.2 + 1.8 years with male predominance. Mean duration of healing was less for Group B having p value <0.001. Group B cases had less wound infection rate and it was found to be statistically significant (p value 0.04 for gross signs of infection and 0.015 for bacterial growth on wound culture). There was significant reduction in post dressing pain in PRP group only after 3rd week of dressing (p 0.009). Conclusion: We conclude that topical PRP is a promising adjunct in treating WSI in addition to other injuries with tissue loss. It can serve as an economical treatment option for rapid healing of WSI patients especially in developing nations.